The dynamics of power in disaster response networks. Issue 4 (24th March 2021) - Boersma, Kees; Ferguson, Julie; Groenewegen, Peter; Wolbers, Jeroen
Abstract: A major challenge for disaster scholars and policymakers is to understand the power dimension in response networks, particularly relating to collaboration and coordination. We propose a conceptual framework to study interests and negotiations in and between various civic and professional, response networks drawing on the concepts of "programming" and "switching" proposed by Manuel Castells in his work on the network society. Programming in disaster response refers to the ability to constitute response networks and to program/reprogram them in terms of the goals assigned to the network. Switching is the ability to connect different networks by sharing common goals and combining resources. We employ these concepts to understand how the US Federal Emergency Management Agency organized its response in the aftermath of Hurricanes Katrina and Sandy. Our conceptual framework can be used both by disaster scholars and policymakers to understand how networked power is constructed and utilized. 摘要: 研究灾害的学者和决策者面临的一个重大挑战是理解灾害响应网络中的权力维度, 尤其与协作和协调相关 (的权力维度). 基于由学者 Manuel Castells 在其网络社会研究中提出的"编程" (programming) 和"转换" (switching) 概念, 我们提出一项概念框架, 研究公民与专家的各类响应网络中及网络之间的利益和协商. 灾害响应中的编程指的是在构成响应网络方面的能力, 并根据分配给网络的各目标对网络进行编程 (program) 或重新编程 (reprogram). 转换指的是通过分享共同目标并结合资源, 以连接不同网络的能力. 我们通过这些概念理解美国联邦紧急事务管理局 (FEMA) 如何组织飓风卡特里娜和飓风桑迪的灾后响应工作. 我们的概念框架能被灾害学者及决策者用于理解网络化的权力是如何被建构和利用的. RESUMEN: Un desafío importante para los especialistas en desastres y los encargados de formular políticas es comprender la dimensión del poder en las redes de respuesta, en particular en lo que respecta a la colaboración y la coordinación. Proponemos un marco conceptual para estudiar intereses y negociaciones en y entre diversas redes de respuesta, cívicas y profesionales, a partir de los conceptos de "programación" y "conmutación" propuestos por Manuel Castells en su trabajo sobre la sociedad red. La programación en respuesta a desastres se refiere a la capacidad de constituir redes de respuesta y programarlas/reprogramarlas en función de las metas asignadas a la red. La conmutación es la capacidad de conectar diferentes redes compartiendo objetivos comunes y combinando recursos. Empleamos estos conceptos para comprender cómo la Agencia Federal para el Manejo de Emergencias (FEMA, por sus siglas en inglés) de los EE. UU. Organizó su respuesta después de los huracanes Katrina y Sandy. Nuestro marco conceptual puede ser utilizado tanto por especialistas en desastres como por legisladores para comprender cómo se construye y utiliza la energía en red.